Deep Structure of the North Natal Valley (Mozambique) Using Combined Wide‐Angle and Reflection Seismic Data. Issue 4 (7th April 2021) - Leprêtre, A.; Schnürle, P.; Evain, M.; Verrier, F.; Moorcroft, D.; de Clarens, P.; Corela, C.; Afilhado, A.; Loureiro, A.; Leroy, S.; d'Acremont, E.; Thompson, J.; et al.
Abstract: The North Natal Valley (NNV) and the Mozambique Coastal Plain (MCP) are key areas for the understanding of the SW Indian Ocean history since the Gondwana break‐up. Nevertheless, the deep structures and the nature of the NNV and MCP remain discussed in the absence of deep geophysical data. In 2016, the NNV, MCP and Limpopo margin (LM) have been investigated along seven wide‐angle and MCS profiles. The combined wide‐angle and reflection seismic interpretation along the N‐S MZ7 profile reveals an upper sedimentary sequence characterized by low velocities generally not exceeding 3 km/s, with thicknesses varying from 0.150 km in the central part to ∼2.8 km in the south. The underlying sequence is formed of a 2.53.0 km thick volcano‐sedimentary sequence which presents important lateral and with depth changes and presence of high velocity lenses, indicating inter‐bedded volcanic sills and recurrent magmatic episodes. The south of the NNV including the Naude Ridge (NR) presents a disturbed sedimentary cover with structural highs and southward‐dipping reflectors and sub‐basins. The crust, reaching 35–40 km onshore below the MCP, gently thins below the continental shelf to a regular thickness of ∼29 km below the NNV. Crustal velocities reveal low velocity gradients, with atypical high velocities. South the ND, the crust thins to 15 km. We interpret the velocity architecture combined with the evidences of volcanism at shallower depths as indicating an intensively intruded continental crust. Contrary to what is proposed in most geodynamic models, the Mozambique Coastal plain and the Natal Valley are both of continental nature, with an abrupt necking zone located south of NR. The Antarctica plate was therefore situated at the eastern limit of these two domains before the Gondwana breakup. Plain Language Summary: About 200 Ma ago, the mega‐continent Pangaea broke up. The dispersion of the pieces of this mega‐continent, linked to the closure and disappearance of the Thetys paleo‐ocean, gave the birth of the Atlantic and Indian Oceans. In detail, the initial position of each piece of this jigsaw is of great importance as it has an impact on the palaeotopography and paleogeography, and our understanding of the genesis of the continental passive margins, the role of tectonic inheritance, the pre‐rift and post‐rift evolution of the topography dynamic (vertical movement) and of the geodynamic of the plates (horizontal movement). Nevertheless, in the Western Indian Ocean, the initial pre‐beak‐up position of Antarctica plate respect to Africa plate is still under debate, mainly due to the lack of deep geophysical data. In 2016, an academic‐industrial collaboration succeeded in acquiring deep information along seven seismic profiles crossing the North Natal Valley off the coast of Mozambique. The results falsify the presence of an oceanic crust in that area and thus most of the plate reconstruction models. They also argue in favor a new paradigm for the genesis of continental passive margin. Key Points: The basement of North Natal Valley and the Mozambique Coastal Plain is of continental nature The location of the COB is South of the Naude Ridge, close to the Ariel Graben location These results preclude the possibility of an overlap of the Antarctica plate on the MCP and the NNV in Gondwana kinematic reconstructions